Literasi Pemahaman Ayat-Ayat Jihad Terhadap Mantan Narapidana Teroris - Sholihuddin, Sholihuddin (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
The Peace Circle Foundation (YLP) is currently experiencing what is called a transformation of religious understanding from extremist to moderate as a result of the Bali bombing tragedy. YLP is an association to empower ex-convicts (former terrorist convicts). One of the causes of radicalization is that it starts from the perspective in understanding religious texts, whether they come from the Al-Qur'an or Hadith. This perspective influences how a Muslim understands how to practice it in everyday life. This research uses a qualitative approach, using observation, interviews and documentation as data collection techniques. The results of this research found that YLP has made efforts to transform religious understanding by embracing ex-convicts and extremist groups to reconstruct their understanding of Islamic teachings. As well as carrying out efforts to prevent radicalism among the general public so that they are not exposed to radicalism and to create peace that reflects Islam as a religion that is rahmatan li al-'alamin.